The Correlation of Sexual Dysfunctions with Chronic Pelvic Pain - Naheed Akhtar , Gul-e-Lala , Faryal Azhar (Journal of Rawalpindi Medical College, 2014)
Background: To describe the correlation of sexual problems in patients presenting with chronic pelvic pain Methods: In this descriptive study, female patients (n=100) sufferer of chronic pelvic pain were included . Their sexual behaviour was assessed by using the questionnaire of Derogatis Interview for Sexual Functioning- Self Report (DISF-SR). This questionnaire contains 5 items which were given scores. A total score was then calculated Results: Patients presenting with chronic pelvic pain having sexual dysfunction were 71% compared with 29% who were sufferer of chronic pelvic pain but without sexual problems. Mean age, BMI and socioeconomic status (monthly family income) was 33. Mean total sexual functioning score of our study sample was 38.28 ± 3.54 while mean and standard deviation for sexual disorders were 9.04± 1.55, 7.12 ± 1.28, 11.23 ± 1.69 and 11.20 ± 1.89 for sexual arousal, behaviour, orgasm and sexual drive respectively. Conclusion: Patients with chronic pelvic pain have some degree of sexual dysfunction and they may suffer from various sexual disorders which need to be assessed so that measures should be undertaken to help these patients to cope with pain and sexual disorders and so they can live a healthy life.